Characterizing complex and competing drug-drug interactions between the antiviral regimen of glecaprevir and pibrentasvir with rifampin or carbamazepine - Matthew P. Kosloski; Hong Li; Stanley Wang; Federico Mensa; Jens Kort; Wei Liu (Wiley, 2023)
Abstract The fixed‐dose combination of the direct acting antivirals glecaprevir (GLE) and pibrentasvir (PIB) is an oral, once‐daily treatment for all six major genotypes of chronic hepatitis C virus infection. A single and multiple‐dose rifampin study (N = 12) and a carbamazepine study (N = 12) were conducted in healthy subjects to evaluate the effects of CYP3A/P‐gp induction and OATP inhibition on the pharmacokinetics of GLE and PIB. In study 1, GLE 300 mg + PIB 120 mg was administered as a single dose either alone, after single and multiple daily doses of rifampin 600 mg, or 24 h after the last rifampin dose. In study 2, GLE 300 mg + PIB 120 mg was administered as a single dose either alone or after multiple doses of carbamazepine 200 mg. Relative to GLE + PIB alone, exposure of GLE was significantly increased by the first co‐administered rifampin dose due to OATP inhibition, significantly decreased 24 h after the last rifampin dose due to CYP3A/P‐gp induction, and slightly increased when co‐administered with steady‐state rifampin due to a combination of inhibition and induction forces. Exposure of PIB was not affected when co‐administered with the first rifampin dose but was significantly decreased with steady‐state rifampin co‐administration, or 24 h after the last rifampin dose due to P‐gp induction. Carbamazepine significantly decreased GLE and PIB exposure, mainly attributed to P‐gp induction. The regimens tested were generally well‐tolerated by the subjects and no new safety issues were identified.